“ChatGPT is the companion, not enemies”: EFL learners’ perceptions and experiences in using ChatGPT for feedback in writing - Mark Feng Teng (Computers and Education: Artificial Intelligence)
The present research was to bridge a research gap in comprehensively understanding students’ perceptions and experiences in utilizing ChatGPT for their writing process in English as a foreign language (EFL) context. The participants were 45 EFL learners in Macau. The study aimed to explore the potential impact of ChatGPT on writing, as well as their perceptions and experiences of ChatGPT in generating feedback for writing. A mixed-methods approach was employed, with quantitative data collected from a questionnaire and qualitative insights drawn from interviews conducted after a semester-long writing course. The findings supported the significant positive effects of AI assistance on writing, including writing motivation, self-efficacy, engagement, and collaborative writing tendency. The qualitative data obtained from the interviews partially corroborated the quantitative findings, although some participants expressed concerns about the use of ChatGPT. Relevant implications and limitations were proposed based on the findings.